Government support to renewable energy R&D: drivers and strategic interactions among EU Member States. Issue 1 (2nd January 2023) - Grafström, Jonas; Söderholm, Patrik; Gawel, Erik; Lehmann, Paul; Strunz, Sebastian
ABSTRACT: Although the climate challenge requires proactive policies that spur innovation in the renewable energy sector, various countries commit vastly different levels of support for renewable energy R&D. This paper addresses the question why this may be the case. Specifically, the objective is to analyse the determinants of government support to renewable energy R&D in the European Union (EU), and, in doing this, we devote particular attention to the question of whether the level of this support tends to converge or diverge across EU Member States. The investigation relies on a data set of 12 EU Member States and a bias-corrected dynamic panel data estimator. We test for the presence of conditional β -convergence, and the impacts of energy dependence and electricity regulation on government R&D efforts. The findings display divergence in terms of government support to renewable energy R&D, and this result is robust across various model specifications and key assumptions. The analysis also indicates that countries with a low energy-import dependence and deregulated electricity markets tend to experience lower growth rates in government renewable energy R&D. The paper ends by discussing some implications of the results, primarily from an EU perspective.